Recycling and Waste Management: A Path Towards a Sustainable Future - Amit Bhumarker Singh; Abhishek Singh (International Journal of Environmental Noise and Pollution Control, 2024)
Waste management is one of the most pressing issues in the world today. This is due to the large amount of trash generated daily, which negatively impacts the environment and various forms of life. Effective waste management aims to dispose of garbage in a manner that minimizes its environmental impact. Waste management plays a crucial role in ensuring that garbage is disposed of in a manner that minimizes environmental impact. There is an urgent need for improved systems for recycling and reusing materials like metals, solvents, batteries, and plastics. As automobiles approach the end of their useful life, recycling becomes essential in reducing and ultimately eliminating waste. This highlights the pressing need for enhanced waste management strategies. Effectively recycling waste can significantly decrease and even eliminate waste generation over time.
Keywords: Waste management; automobiles; metals; recycling; reusing